(untitled) (CIPEEX, 2025)
Public trust in Brazil’s electronic voting machines is crucial, especially in a climate marked by political polarization and the spread of misinformation. Far from being a mere voter collection device, the machine represents a sophisticated system, involving processes such as cryptographic key generation, public audits, and technological protection mechanisms, such as shielded USB ports and printers with anti-fraud technology. The Superior Electoral Court (TSE) conducts public security tests, inviting experts to identify potential flaws, in a continuous effort toward transparency and improvement. This study aimed to analyze the security of the electoral process, focusing on its transparency, auditability, and system reliability. The methodology adopted was bibliographic research, based on scientific articles and audiovisual material produced by the Electoral Court of Santa Catarina. The results demonstrate that the system is developed with an emphasis on security at all stages, from software development to vote counting, utilizing resources such as digital signatures, function segmentation, audit logs, and open source code. These measures are part of the "defense in depth" strategy, which combines logical, physical, and procedural protection. The Brazilian electoral process allows for extensive oversight, from voter registration to the certification of elected officials. Even so, the impact of persuasive communication on public perception is recognized, which can strengthen or weaken institutional trust. It is concluded that the reliability of electronic voting machines derives from the combination of robust technology, transparency mechanisms, and public credibility, which are vital foundations for democratic legitimacy.